The influence of age on household savings behaviours and motives: Evidence from Spain - Fernando Lera Lopez (European Regional Science Association (ERSA), 1998)
The role which savings play in the economy is beyond the scope of discussion. Hence, the prolonged fall of the family savings rate has caused great worry in developed countries. In Spain, this situation is especially serious with falls beyond the family savings rate. In this context it is absolutely necessary try to understand what the reasons are for savings and what are the variables which have a determined influence on savings. This paper intends to define the socio-demographic variables which determine the behaviour, from an analysis of an average inhabitant of Navarre in terms of financial savings. According to a survey of 1,000 people in Navarre, it is shown that the age can explain not only the savings behaviour of families but also the motives and attitudes. Moreover, the defining capacity and differential of the age in the behaviour of average citizens of Navarre is reflected primarily in the savings motives of particular citizens of Navarre. Similarly, taking into account the savings motives, the authorities can apply appropriate policies in order to increase the level of family savings and achieve sustainable growth in a time of macroeconomics magnitudes.
Keywords: 330